DOI: 10.4018/978-1-60566-280-0.ch008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Doppler Embolic Signals

Abstract: A broad view on the analysis of Doppler embolic signals is presented, uniting physics, engineering and computing, and clinical aspects. The overview of the field discusses the physiological significance of emboli and Doppler ultrasound with particular attention given to Transcranial Doppler; an outline of high-performance computing is presented, disambiguating the terminology and concepts used thereafter. The presentation of the major diagnostic approaches to Doppler embolic signals focuses on the most signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Finally some concluding studies reported the Short Time Modified Covariance and the remarks are drawn highlighting possible application of the discrete Choi-Williams distribution as good alternatives to the method. conventional method, when applied to arterial blood flow Doppler signals [1][2][3].II TIME-FREQUENCY METHODOLOGY Recently, it was noted that with time-frequency representation it was difficult to observe important events Each bin of a time signal contains information about all the occurring during the systolic phase of the cardiac cycle blood cells in the sample volume at a given time. The time (vortex n systol1c drop or embol1c events durg systole) This iS because the highest velocities of blood occur during observed anywhere in the signal.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Finally some concluding studies reported the Short Time Modified Covariance and the remarks are drawn highlighting possible application of the discrete Choi-Williams distribution as good alternatives to the method. conventional method, when applied to arterial blood flow Doppler signals [1][2][3].II TIME-FREQUENCY METHODOLOGY Recently, it was noted that with time-frequency representation it was difficult to observe important events Each bin of a time signal contains information about all the occurring during the systolic phase of the cardiac cycle blood cells in the sample volume at a given time. The time (vortex n systol1c drop or embol1c events durg systole) This iS because the highest velocities of blood occur during observed anywhere in the signal.…”
mentioning
confidence: 99%
“…Finally some concluding studies reported the Short Time Modified Covariance and the remarks are drawn highlighting possible application of the discrete Choi-Williams distribution as good alternatives to the method. conventional method, when applied to arterial blood flow Doppler signals [1][2][3].…”
mentioning
confidence: 99%
See 1 more Smart Citation